CRISPR/CAS9 IN GENOME EDITING: A NATURE GIFTED MOLECULAR TOOL - Bashir, MA; Ali, Q; Rashid, MS; Malika, A (Biological and Clinical Sciences Research Journal, 2020)
The Cas9 protein derived from type II CRISPR as a part of bacterial immune system has been raising up as a useful genetic tool for genomic engineering in various life forms. As RNA-guided DNA endonucleases, the Cas9 could be effectively customized to marked new DNA sequence sites by adjusting guided RNA sequences; it has been appeared as new emerging DNA editing technology. The nuclease-disable types of Cas9 has provided adaptable RNA guided DNA focusing on regulation and visualization of genomic DNA, just as for restoring the epigenetic forms and status, all has been shown in a an accurate sequence. Through these proceed; the researchers have started to explore conceivable uses of Cas9 in medical, agriculture, pharmaceutical and livestock sciences.